Adenocarcinoma ileum: a rare cause of ileal stricture mimicking intestinal tuberculosis: a case report and literature review - Aggarwal, Manisha; Manchikanti, Dinesh; Kundaikar, Janitta; Thomas, Shaji; Arsia, Ashish; Pusuluri, Rahul; Meena, Kusum; Kumar, Sanjay (International Surgery Journal, 2021)
One of the commonest causes of small intestinal obstruction in India is tuberculosis. The terminal ileum and ileocaecal junction are the most common sites of small bowel involvement, and the most common abnormality is short-segment strictures. We report a patient who presented with small intestinal obstruction due to a solitary ileal stricture, but turned out to be a rare condition that can mimic intestinal tuberculosis. A 60-years-old man, with recurrent episodes of pain abdomen for 1 year, presented to our surgical emergency with evidence of small intestinal obstruction. A CT scan revealed a short segment stricture (2.7 cm) in mid ileal loop with luminal narrowing and marked proximal dilation of proximal ileal loops with a few sub centimetric mesenteric lymph nodes. On laparotomy with a suspected diagnosis of intestinal tuberculosis, it turned to be an adenocarcinoma of the ileum- a rare condition that can mimic intestinal tuberculosis. One of the commonest causes of small intestinal obstruction in India is abdominal tuberculosis. However, all cases of small intestinal obstruction are not tuberculosis. Adenocarcinoma of ileum is a very rare entity. This case report shows that a surgeon should have a high index of suspicion in an elderly patient presenting with small intestinal obstruction, with CT demonstrating isolated short-segment small bowel thickening, as it could be a presentation of obstructing type adenocarcinoma of the small intestine.